2007
DOI: 10.1259/dmfr/32238405
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic and arthrographic diagnoses of synovial chondromatosis

Abstract: Synovial chondromatosis (SC) is rare in the temporomandibular joint (TMJ). Plain radiographs, CT, MRI and arthrography of the TMJ have been used for the diagnosis of SC. The purpose of this paper is to present ultrasonographic and arthrographic diagnoses of a case of SC of the TMJ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A review of the literature revealed a total of 10 articles [5, [15][16][17][18][19][20][21][22][23] published between 2007 and 2017, with a total of 79 cases (59 female and 20 male patients) ( Table 3). The average age at diagnosis was 44.8 years (range 21-74 yrs).…”
Section: Resultsmentioning
confidence: 99%
“…A review of the literature revealed a total of 10 articles [5, [15][16][17][18][19][20][21][22][23] published between 2007 and 2017, with a total of 79 cases (59 female and 20 male patients) ( Table 3). The average age at diagnosis was 44.8 years (range 21-74 yrs).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it allowed us to indirectly detect some small non-calcified nodules which were overlooked by MRI. Li et al 15 also reported the usefulness of arthrography in SC of the TMJ. A more detailed picture of the cavity could be obtained using CBCT during TMJ arthrography, thanks to the high spatial resolution of CBCT.…”
Section: Discussionmentioning
confidence: 99%